2004
DOI: 10.1080/09670260410001710114
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of ubiquitin and proteasomes in spermatids during spermiogenesis ofChara vulgaris(Charophyceae)

Abstract: Immunocytochemistry with anti-ubiquitin and anti-proteasome antibodies revealed antigenic signals in spermatids of Chara vulgaris in all ten spermiogenesis phases defined on the basis of morphological features. The strongest antigenic signals, indicating the presence of both ubiquitin and proteasome, were observed mainly in the cytoplasm in early and midspermiogenesis (phases II -V). During the transition of histone into protamine-type proteins, stronger anti-ubiquitin and anti-proteasome antigenic signals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Immunocytochemical studies with anti-ubiquitin and antiproteasome antibodies has revealed antigenic signals in spermatids during all ten stages of spermiogenesis in Chara vulgaris [36]. In early and mid spermatids (stages II-VI) the strongest antigen signals indicating the presence of proteasomes and ubiquitin have been observed in cytoplasm.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Immunocytochemical studies with anti-ubiquitin and antiproteasome antibodies has revealed antigenic signals in spermatids during all ten stages of spermiogenesis in Chara vulgaris [36]. In early and mid spermatids (stages II-VI) the strongest antigen signals indicating the presence of proteasomes and ubiquitin have been observed in cytoplasm.…”
Section: Introductionmentioning
confidence: 96%
“…However, to the best of our knowledge the ubiquitin-proteasome system has been investigated only in C. vulgaris [34][35][36].…”
Section: Introductionmentioning
confidence: 99%